NMDA receptor activation is downstream coupled to pannexin 1 opening by Src kinase in dorsal horn neurons: an essential link for mechanical hyperalgesia in nerve-injured rats - CONSTANDIL, LUIS (Usach, 2024)
Summary data book NMDA receptor activation is downstream coupled to pannexin 1 opening by Src kinase in dorsal horn neurons: an essential link for mechanical hyperalgesia in nerve-injured rats PAIN-D-24-00602_R1
Keywords: Ciencias Biológicas; Medicina Básica; NMDA receptor, Src protein kinase, Pannexin 1, Neuropathic pain, Mechanical hyperalgesia, Spinal cord